TINGKAT PEMAHAMAN PENGUNJUNG TERHADAP HUTAN KOTA BUKIT CADIKA DAN MANFAATNYA BAGI LINGKUNGAN HIDUP DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Saswita, Desi; Sribudiani, Evi; Sulaeman, Rudianda (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The higher growth of urban people and development of advanced technologies caused on a huge conversion on green areas to become public office, supermarket, industrial purpose, etc which decreasing the ecosystem sustainability of urban environment. One of offorts to manage urban environment, such as building urban forest. Urban Forest Cadika Hill is located on Bangkinang District, Kampar Regency. This area is usually used for camping, recreational purpose and sports facilities for local communities. Despite of its popularity and multifunctional purpose, there are lots of troubles such as waste problem, security issue and plant damage which are caused by huge. This research is conducted to analyze visitor’s understanding level of urban forest and its benefit for environmental data was collected by using survey method through interview and questionnaires that had been prepared. To achieve the aim of research, data obtained was analyzed by descriptive. To know the level of visitors understanding might seen from the score that determined. The results show the level of visitors understanding to urban forest in Cadika Hill categorized to be high with score 36,71 and also the level of understanding to environment with score 37,32. Keywords: Understanding Level, Urban Forest, Environment